Decolonizing Sociology Through Collaboration, Co‐Learning and Action: A Case for Participatory Action Research - Fahlberg, Anjuli (Sociological forum (Randolph, N.J.), 2023)
Despite important efforts by postcolonial scholars to “decolonize” sociology, this endeavor remains limited by the scaffolding of empirical research, or the institutionalized practices and beliefs embedded within data collection and researchers' relationship to research subjects. In its current form, this scaffolding excludes “subaltern” voices from critiquing and extending sociological theory, deriving benefits from the study, or informing social actions that stem from the research. This limits the field's understanding of the multi‐faceted impacts of colonialism and retrenches inequalities between scholars and participants. Participatory Action Research (PAR) offers an alternative, decolonial infrastructure. PAR acknowledges the value of knowledge from the periphery and calls for (1) the participation of marginalized research populations in each step of the research process; (2) co‐learning between researchers and participants; and (3) collaborative social action that centers the needs of marginalized research populations. Drawing on a case study of PAR in Rio de Janeiro, I demonstrate how PAR allows sociologists, in partnership with historically colonized groups, to decolonize sociology not only in theory, but in the concrete practices of empirical research.